Pelatihan Penulisan Laporan dan Artikel Penelitian Tindakan Kelas (PTK) bagi Guru-guru SMA - Suripah, Suripah; Nurhuda, Nurhuda; Abdurrahman, Abdurrahman; Atiqah, Nur (Community Education Engagement Journal, 2024)
This service activity is motivated by the problem that some teachers still have in writing reports and creating classroom action research (PTK) articles which have been carried out by the teachers themselves. For this reason, this community service activity needs to be carried out with the aim of providing training related to writing reports on the results of classroom action research and writing in the form of scientific publication articles to high school teachers, especially at SMA Negeri 3 Siak Hulu, Kampar Regency Jl. Purwosari, Pandau Jaya Village, Siak Hulu District, Kampar Regency, Riau. It is hoped that this training will help teachers in preparing final reports on classroom action research and also publishing them in the form of scientific articles in accredited national journals. Activity methods include training, workshops and simulations. The results of these PkM activities are that teachers have good perceptions and responses to the implementation of activities. The teachers are enthusiastic and have a strong desire to write in the hope that their articles can be accepted and published in accredited national journals